2017
DOI: 10.26905/jkdp.v21i3.1489
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Financial Literacy for Growing Personal Finance

Abstract: Financial literacy played an important role for everyone in managing personal finances. This research aimed to determine how the level of financial literacy in students S1 Faculty of Economics and Business, Universitas Pasundan and investigate what factors are influencing it. The observed respondents were students from the Faculty of Economics and Business, Universitas Pasundan. The research data was collected through questionnaires, descriptive analysis, and test multinomial logit. Based on the results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
2
17
0
7
Order By: Relevance
“…Theodora & Marti'ah (2016) stated that generally, financial literacy is critical to help someone manage money independently and make the appropriate financial planning. Knowledge and understanding related to personal finances will affect students in making good and wise financial decisions (Gunardi, Ridwan, & Sudarjah, 2017). Sabri & Falahati (2012) showed that financial literacy has a positive and significant impact on financial well-being of college students.…”
Section: Financial Literacymentioning
confidence: 99%
“…Theodora & Marti'ah (2016) stated that generally, financial literacy is critical to help someone manage money independently and make the appropriate financial planning. Knowledge and understanding related to personal finances will affect students in making good and wise financial decisions (Gunardi, Ridwan, & Sudarjah, 2017). Sabri & Falahati (2012) showed that financial literacy has a positive and significant impact on financial well-being of college students.…”
Section: Financial Literacymentioning
confidence: 99%
“…A private company in the US has conducted a financial literacy survey for the benefit of expanding its product (Volpea, Chen, & Liu, 2006). Another study has also examined on how demographic variables affect students financial literacy (Gunardi, Ridwan, & Sudarjah, 2017). In addition, previous studies have indicated on how the level of financial literacy affecting personal financial planning.…”
Section: |mentioning
confidence: 99%
“…In fact, financial difficulties often arise due to financial management mistakes, instead of low income. Gunardi, Ridwan, & Sudarjah (2017) claim that financial literacy plays a big role in the financial management of individuals. A range of previous studies investigating the effect of financial literacy index on MSMEs financial management such as Muzdalifa, Rahma, & Novalia (2018) and Anggraini (2015) state that financial literacy index influences financial management in MSMEs.…”
Section: The Effect Of Financial Literacy Index On the Financial Inclmentioning
confidence: 99%